The examination of pecan price differences using spatial correlation estimation (2005)
A spatial analysis is used to model factors that explain the price received by pecan growers. Besides the statistical aspect of the study focussing on spatial utoregressive residuals, the economic analysis of the paper identifies linkages between the price for in-shell pecans received by growers and the characteristics of the orchard, production costs and resources, and the orchard location.